In-Situ Synthesis of Silver Nitrate incorporated with Polysulfone Membrane Characterization: Effect of Ag Precursor - Ahmad, Azlinnorazia; Yunos, Muhamad Zaini (International Journal of Integrated Engineering, 2019)
Water treatment using membrane filtration is one of the common methods that can generate higher amount of quality water in future. However, polymer blending method via ex-situ synthesis method shows some weaknesses on membrane modification such as membrane prone to fouling and hydrophobic. In this present work, the characterization of in-situ synthesis of silver nitrate (AgNO3)/polysulfone (PSf) membrane was carried out for water separation purposes. The characterization of in-situ synthesis of AgNO3 in PSf membrane has been investigated with the present of silver (Ag) precursor. The Ag/precursor dope solution thermodynamic stability was evaluated via ternary phase diagram. The membrane was characterized in term of morphology, existence of element and membrane surface roughness. The performance of AgNO3 was highly influences by PSf/alkali characterization. The interaction of PSf/AgNO3/precursor reduced thermodynamic stability of the dope solution and increased the phase inversion rate between polymer and solvent and led to more porous sub layer with larger irregular finger like pores.  In addition, high molecular weight of alkali reacts with AgNO3 effectively and resulted on higher membrane surface roughness where it is increased up to 58 % causing higher surface area of the membrane. The amorphous peak is due to the presence of alkali in the membrane during the XRD analysis. The intensity of these peaks tended to decrease upon addition of silver in PSf membrane, as compared to regular polymer blending method of Ag on PSf membrane. Thus, in-situ synthesis of silver has potential to be used as a method in membrane fabrication as it enhances membrane performance for water separation.